Body Freedom Flutter of a Blended Wing Body Model Coupled with Flight Control System. (2015) - Yingsong, Gu; Zhichun, Yang; Shun, He
Abstract: Aeroservoelastic model is developed for a blended wing body aircraft coupled with flight control system. Body freedom flutter of such aeroservoelastic system is analyzed and trend studies considering varied loop gain value, center of gravity of the balanced weight and wing stiffness are delivered to determine their influence on body freedom flutter characteristics of this aeroservoelastic system. It is found that the closed loop flutter speed decreases dramatically compared to that of the open loop case. The loop gain value and the wing stiffness have strong influence on the closed loop flutter characteristics. It is noted that the static unstable unaugmented blended wing body aircraft can be stabilized by proper designed flight control system, however, the closed loop body freedom flutter speed is still quite low which needs further consideration in flight control system synthesis.